Kecenderungan Penumpang Menggunakan Moda Kereta Api Antar Kota Dengan Penerapan Protokol Kesehatan Di Era New Normal (Politeknik Perkeretaapian Indonesia Madiun, 2022)
ABSTRACT Health protocol during Covid 19 Pandemic however can reduce the tendency of passengers in using trains as mode of transportation. The inter-city train health protocol is regulated in a circular letter from the Minister of Transportation regarding the guidelines and technical guidelines for rail transportation in the new normal era. The description of the behavior of inter-city train passengers with the application of health protocols is needed as a consideration in implementing further policies. This study uses situational variables, knowledge and personality as predictors of passengers' decisions to use trains with the application of health protocols. The research sample was 96 with random sampling technique. The data that has been collected is then tested with binary logistic regression to generate the tendency of passengers to use trains with the application of health protocols in the new normal era. The results of the study show that situational variables and passenger personalities influence passenger decisions in using the train mode in the new normal era. Keywords: Health protocol, new normal era, consumer behavior, binary logistic regression